Physiological and productive performance of hop (Humulus lupulus L.) varieties grown under subtropical conditions in Brazil - Neves, Caio Scardini [UNESP]; Aires, Eduardo Santana [UNESP]; Campos, Olivia Pak [UNESP]; Fortuna, Gabriel Cássia [UNESP]; de Oliveira Gomes, Jordany Aparecida [UNESP]; Callili, Daniel [UNESP]; Ono, Elizabeth Orika [UNESP]; Rodrigues, João Domingos [UNESP]; Bonfim, Filipe Pereira Giardini [UNESP] (Southern Cross Publishing, 2024)
The primary focus of hop cultivation is the brewing industry. Brazil is one of the largest producers and consumers of beer worldwide and therefore one of the largest importers of hops. Therefore, it is essential to develop research that promotes the national production of hops. This study aimed to analyze the photosynthetic, morphometric and productive capacities of five hop varieties outside of their natural cultivation conditions in a subtropical climate; thus, to analyze the performance of post-tropicalized hops. A randomized block experimental design was used, including five cultivar treatments (Comet, Chinook, Cascade, Nugget and Columbus varieties) with four blocks and two plants per plot, totaling 20 plots and 40 sampling units. Physiological, morphometric and productive data were collected during the reproductive phase (final phase of plant development). Photosynthetic data were collected using an infrared gas analyzer (IRGA) coupled to a portable fluorometer to obtain gas exchange and fluorescence data. The collected morphometric and productive data are related to the vegetative and productive capacity of the hops. All varieties analyzed showed remarkable physiological responses. However, the highest quantum yield and effective yield of PSII were obtained from Comet (0.94 and 0.50) and Nugget (0.94 and 0.52), respectively. Comet exhibited the best morphometric results related to vegetative development (561.12 cm for plant height) but did not exhibit similarly high productive performance, while Cascade was the variety with the best productivity. Moreover, this work shows that tropicalized hops have satisfactory performance.
Keywords: Cannabaceae; fluorescence; gas exchange; Humulus lupulus L; morphometric; productivity